Clonality of Bacterial Pathogens Causing Hospital-Acquired Pneumonia - Pudová, V; Htoutou Sedláková, M; Kolář, M; Working Group (Current microbiology, 2016)
Hospital-acquired pneumonia (HAP) is one of the most serious complications in patients staying in intensive care units. This multicenter study of Czech patients with HAP aimed at assessing the clonality of bacterial pathogens causing the condition. Bacterial isolates were compared using pulsed-field gel electrophoresis. Included in this study were 330 patients hospitalized between May 1, 2013 and December 31, 2014 at departments of anesthesiology and intensive care medicine of four big hospitals in the Czech Republic. A total of 531 bacterial isolates were obtained, of which 267 were classified as etiological agents causing HAP. Similarity or identity was assessed in 231 bacterial isolates most frequently obtained from HAP patients. Over the study period, no significant clonal spread was noted. Most isolates were unique strains, and the included HAP cases may therefore be characterized as mostly endogenous. Yet there were differences in species and potential identical isolates between the participating centers. In three hospitals, Gram-negative bacteria (Enterobacteriaceae and Pseudomonas aeruginosa) prevailed as etiological agents, and Staphylococcus aureus was most prevalent in the fourth center.
Keywords: jednotky intenzivní péče; Intensive Care Units; Phylogeny; Cross Infection; Pneumonia; Bacteria; pneumonie; lidé; infekce spojené se zdravotní péčí; Humans; fylogeneze